Food Intake and Nutritional Status among Adults: Sharing the Malaysian Experience - Ahmed, Ferdoushi; Siwar, Chamhuri (Pakistan Journal of Nutrition, 2013)
Nutritional status of the people of a country is mainly influenced by the food they intake regularly. Taking improper amount of food results in mal-nutrition (i.e., overweight, obese or under nutrition) which ultimately affects physical well-being of the people. Nutritional status of people is also closely linked with dietary fat intake. This paper focuses on food intake and nutritional status among adults in Malaysia. The paper reviews currently available information on dietary food intake and nutritional status of Malaysian adults. Literatures were identified for review through a comprehensive search by using electronic and non-electronic databases. Based on the review of literature, it was found that nutritional status of Malaysian adults is significantly correlated with their habit of food intake. Studies revealed that the persons who over estimate their dietary fat intake has significantly higher adjusted mean Body Mass Index (BMI) (25.79±0.76) than accurate estimators (24.09±0.42) or under-estimators (24.06±0.49). Moreover, the group of over-estimators has the highest proportion of overweight and obese (60%) compared to under-estimators (40.8) and accurate estimators (31.6%). The adjusted mean Waist Circumference (WC) is also comparatively higher among the persons who over estimate their dietary fat intake. It was reported that overweight and obesity are highly endemic in Malaysia. Overweight and obesity result in diabetes, hypertension and coronary heart diseases which cause premature deaths. Therefore, future research is urgently needed at both household and national level for further understanding the correlation between dietary food intake and nutritional status and consequently physical well-being of the people in the country.